Effect of body weight on memory function among undergraduate students in health campus Universiti Sains Malaysia - Pereira, Angela Sharlyn (Universiti Sains Malaysia, 2023)
Acknowledging and maintaining a healthy body weight is essential among students as it has a diverse effect on overall health. A good memory function according to a healthy body weight is crucial to enhance the quality of life. Thus, a cross-sectional study was carried out to detect the association between body weight on memory function among undergraduate students in USM. Data was collected through Google form. A total of 151 students from the Health Campus, USM who fulfilled the inclusion criteria were involved. They were chosen through a stratified random sampling method. Data was analysed using the Statistical Package for Social Science (SPSS) version 27. This study showed that 43.8% of overweight students showed delayed memory recall. There is a statistical association between body weight on memory function (p < 0.05).